Design, modelling and biofabrication of scaffolds for osteochondral repair - Ferro Barbosa, Cristina (2024)
Osteochondral (OC) defect refers to a focal area of injury that involves both the cartilage and a piece of underlying bone, occurring often as a result of traumas or degenerative illnesses such as osteoarthritis (OA). Currently, numerous orthopaedic procedures are used for repairing the damage of the OC lesions, but none of these treatments have been able to accomplish a full repair of an OC defect. Over the past two decades, the field of tissue engineering has provided a prospective alternative strategy using biomaterials and cells in a scaffold. Extrusion- based three-dimension printing (3D) technology has achieved advancements in bone and cartilage reconstruction, providing a new strategy for restoring joint function. The aim of this research was to design and manufacture a multi-material graded OC scaffold that mimics the cartilage and bone interface with the specific graded mechanical properties. A novel approach involves addressing the complexity of an OC scaffold by aiming to mimic the four zones of the cartilage and the subchondral zone. Following Kabir et al., discovery regarding the mechanical properties of the cartilage within OC tissue, the research strategy proposed designing a scaffold with no bounding, this focus on achieving the desired mechanical characteristics of an OC scaffold. Kabir et al., study reported a compressive modulus of 10.60 ± 3.62 MPa for cartilage within OC tissue under unconfined compression, which served as a foundational reference. To implement this into the strategy, the materials chosen were polycaprolactone (PCL) to provide structural support and gelatin methacrylate (GelMA) to act as a cell carrier. These materials possess properties that make them well-suited to processing through the extrusion technique, utilising the 3D Discovery RegenHu machine, allowing the co-printing of these two materials. Three geometries, square, sinusoidal, and spiral, were investigated to vary the mechanical properties in the OC scaffold. The results demonstrate intriguing trends in Young's modulus across various scaffold geometries. Integration of these geometries into a unified OC scaffold yielded a Young's modulus of 50.68 ± 3.38MPa after 14 days of cell culture, surpassing the mechanical properties of individual designs. Moreover, viability assessment studies were performed on the PCL/GelMA scaffolds. The findings indicate that the scaffold designs support cell proliferation, as shown in DNA quantification. The findings in this thesis therefore support the feasibility of using extrusion-based 3D printed scaffolds for repair of OC defects.